Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 13 - Cumulative Review: 42

Answer

$21-4\sqrt 5$

Work Step by Step

$(2\sqrt 5-1)^{2}$ =$(2\sqrt 5-1)(2\sqrt 5-1)$ =$2\sqrt 5(2\sqrt 5-1)-1(2\sqrt 5-1)$ =$(2\sqrt 5)^{2}-2\sqrt 5-2\sqrt 5+1$ =$4(5)-4\sqrt 5+1$ =$20-4\sqrt 5+1$ =$21-4\sqrt 5$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.